Purslane: The Reigning Champion of Vitamins A and E among Vegetables and a Potential Crop for Home Gardens - Xueyan Zhang; Mary Dixon; Guodong Liu (EDIS, 2024)
Purslane is often labeled as a noxious weed in Florida; however, this seemingly pesky plant is perceived as a nutritional powerhouse in Asia and other continents. Levels of vitamin A and E in purslane far surpass those found in broccoli, tomato, and lettuce. A mere 3.5 ounces of purslane can fulfill 81% of an individual's daily vitamin requirements, and up to half a pound can meet the daily needs for both Vitamins A and E. Sustaining this nutritional wealth hinges on the timing of harvest when purslane plants attain a height of 5 to 6 inches. Beyond this stage, purslane becomes excessively fibrous and aged, making it unsuitable for consumption and necessitating removal through weeding. This publication article provides a comprehensive overview of purslane, delving into its botany, garden production, harvest practices, and both culinary and medicinal uses to assist growers and consumers in understanding when to savor its nutritional benefits and when to weed it from farmlands.